Modified measuring compass as an intraoral paralleling device - Patil Pravinkumar (Wolters Kluwer Medknow Publications, 2010)
This article describes a simple technique of useful modification of measuring compass, procured from a school compass box, to make an intraoral paralleling device. This device is useful in examining parallelism of tooth or implant abutment preparations for a common path of placement in fixed dental prostheses. It can be used to examine the parallelism of guiding planes in removable partial denture patients as well.